Green Tea Extract (GTE) improves differentiation in human osteoblasts during oxidative stress - Vester, Helen (BioMed Central, 2014)
BACKGROUND: Oxidative stress is involved in the pathogenesis of bone diseases such as osteoporosis, which has a high coincidence with fractures in elderly. Several studies showed positive effects of herbal bioactive substances on oxidative stress. This study analyses the effect of green tea extract (GTE) Sunphenon 90LB on primary human osteoblasts differentiation and viability during H(2)O(2)-induced oxidative stress. Moreover, it was analyzed, whether GTE acts during the HO-1 signaling pathway. METHODS: Human osteoblasts were isolated from femoral heads of patients undergoing total hip replacement. Beneficial effects of GTE on osteoblasts were examined in a dose- and time-dependent manner. Furthermore, GTE was given before, simultaneous with and after induction of oxidative stress with 1 mM H(2)O(2) to simulate prophylactic, acute and therapeutic use, respectively. Cell damage was measured by LDH leakage and cell viability by MTT assay. Flow cytometry was applied to measure formation of Reactive Oxygen Species by using 2`7`-dichlorofluorescein-diacetate. The formation of Extracellular Matrix after differentiation with GTE supplementation during oxidative stress was visualized with von Kossa and Alizarin Red staining. Last one was additionally photometrically quantified. To assess the effects of H(2)O(2) and GTE on the osteogenic genes, RT-PCR was performed. To evaluate the intramolecular influence of GTE after the stimulation the protein levels of HO-1 were analyzed. RESULTS: Stimulation of primary human osteoblasts with low doses of GTE during oxidative stress over 21 days improved mineralization. Furthermore, GTE supplementation in combination with H(2)O(2) leads to a higher gene expression of osteocalcin and collagen1α1 during osteoblasts differentiation. Both are important for bone quality. Pre-incubation, co-incubation and post-incubation of osteoblasts with high doses of GTE protect the osteoblasts against acute oxidative stress as shown by increased cell viability, decreased LDH leakage, and reduced production of intracellular free radicals. Functional analysis revealed an increased HO-1 protein synthesis after stimulation with GTE. CONCLUSIONS: Incubation of human primary osteoblasts with GTE significantly reduces oxidative stress and improves cell viability. GTE also has a beneficial effect on ECM production which might improve the bone quality. Our findings suggest that dietary supplementation of GTE might reduce inflammatory events in bone-associated diseases such as osteoporosis.